Memory B cells and plasma cells: The differentiative continuum of humoral immunity - Cancro, Michael P.; Tomayko, Mary M. (Immunological reviews, 2021)
Summary Immunological memory is a composite of lasting antibody titers maintained by plasma cells in conjunction with memory T and B cells. Memory B cells are a critical reservoir for plasma cell generation in the secondary response. Identification of memory B cells requires that they be distinguished from naïve, activated, and germinal center precursors and from plasma cells. Memory B cells are heterogeneous in isotype usage, immunoglobulin mutational content, and phenotypic marker expression. Phenotypic subsets of memory B cells are defined by PD‐L2, CD80, and CD73 expression in mice, by CD27 and FCRL4 expression in humans and by T‐bet in both mice and humans. These subsets display marked functional heterogeneity, including the ability to rapidly differentiate into plasma cells versus seed germinal centers in the secondary response. Memory B cells are located in the spleen, blood, other lymphoid organs, and barrier tissues, and recent evidence indicates that some memory B cells may be dedicated tissue‐resident populations. Open questions about memory B cell longevity, renewal and progenitor‐successor relationships with plasma cells are discussed.